Regulatory Functions of Nilaparvata lugens GSK-3 in Energy and Chitin Metabolism - Ding, Yan-Juan; Li, Guo-Yong; Xu, Cai-Di; Wu, Yan; Zhou, Zhong-Shi; Wang, Shi-Gui; Li, Can (Frontiers in Physiology, 2020)
Glucose metabolism is a biologically important metabolic process. Glycogen synthase kinase (GSK-3) is a key enzyme located in the middle of the sugar metabolism pathway that can regulate the energy metabolism process in the body through insulin signaling. This paper mainly explores the regulatory effect of glycogen synthase kinase on the metabolism of glycogen and trehalose in the brown planthopper (Nilaparvata lugens) by RNA interference. In this paper, microinjection of the target double-stranded GSK-3 (dsGSK-3) effectively inhibited the expression of target genes in N. lugens. The content of glycogen and glucose decreased significantly at 48 h and 72 h after dsGSK-3 injection. The content of trehalose increased significantly at 48 h after injection and decreased significantly at 72 h. At the same time, two trehalase activities were significantly reduced at 48 h and 72 h after injection. At 48 h and 72 h after dsGSK-3 injection, the expression of three TRE genes decreased or decreased significantly, and the expressions of GP, GS, TPS1 and TPS2 decreased significantly. In addition, the expression of three chitin synthase genes was different at 48 h after dsGSK-3 injection; however, the expression of CHS1 was not significantly changed, the expression of CHS1a was significantly increased, and the expression of CHS1b was significantly decreased; at 72 h after injection, the expression of all three CHS was significantly down-regulated. The expression of G6PI was also significantly reduced at 72 h after dsGSK-3 injection. At 72 h after the injection of glucose or trehalose with dsGSK-3, glycogen and glucose levels increased significantly or returned to levels similar to dsGFP but had no significant effect on the trehalose content. These results indicated that a low expression of GSK-3 can regulate the metabolism of glycogen and trehalose by regulating the expression of insulin signaling pathway and energy metabolism pathway-related genes, and can regulate the expression of genes related to the chitin biosynthesis pathway in N. lugens. The relevant research results will help us to more comprehensively explore the molecular mechanism of the regulation of energy and chitin metabolism of insect glycogen synthase kinases in species such as N. lugens.